2018
DOI: 10.18172/cig.3378
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological dynamics in a small catchment with silvopastoral land use in SW Spain

Abstract: Please, cite this article as: Schnabel, S., Lozano Parra, J., Gómez-Gutiérrez, A., Alfonso-Torreño, A. 2018. Hydrological dynamics in a small catchment with silvopastoral land use in SW Spain. P A P E R A C C E P T E D . P R E -P R I N T V E R S I O N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…event 36). Our results are also in agreement with the observations made by Schnabel et al [73], who observed higher runoff contributions for low rainfall intensities events occurring in periods with high soil water content than for events with high rainfall intensities. Besides, those authors pointed out that this condition was common during years with above average rainfall (i.e., during wet years) but was rarely observed during dry years.…”
Section: Non-linearity Assessment At Es Fangar Catchmentsupporting
confidence: 94%
“…event 36). Our results are also in agreement with the observations made by Schnabel et al [73], who observed higher runoff contributions for low rainfall intensities events occurring in periods with high soil water content than for events with high rainfall intensities. Besides, those authors pointed out that this condition was common during years with above average rainfall (i.e., during wet years) but was rarely observed during dry years.…”
Section: Non-linearity Assessment At Es Fangar Catchmentsupporting
confidence: 94%
“…The high spatial and temporal variability of the hydrological processes in semi-arid areas makes it difficult to study and to model the hydrological response of catchments in these regions [69,70]. In the particular case of SW Iberian Peninsula, various studies carried out in small catchments representative of dehesas [41,60,61] analyzed the influence of rainfall variability on runoff generation. At the event scale, these studies evidenced the importance of antecedent soil moisture conditions on channel flow production.…”
Section: Discussionmentioning
confidence: 99%
“…The annual discharge data available for the Guadalperalón catchment corresponded to 5 hydrological years in the period between 1991 and 1997. A description of the equipment and methods used to obtain the discharge data can be found in [41,60,61]. Finally, the relationship between the values of (S c /V max ) req obtained from Equation (3) and the respective annual rainfall data (P annual ) was analyzed, in order to estimate a minimum reference value of the S c /V max ratio required for the study area.…”
Section: Influence Of Catchment Areamentioning
confidence: 99%
“…These studies provide data enabling assessment of the implications of global change for catchment water resources and soil conservation (Lana-Renault et al, 2018). In addition, they show the relevance of long-term monitoring sites for (interdisciplinary) environmental research and management (Holzmann, 2018;Gascuel-Odoux et al, 2018), especially in areas having high and very high rainfall variability (Rodríguez-Caballero et al, 2018;Schnabel et al, 2018).…”
Section: This Volume Of Cuadernos De Investigación Geográfica-geograpmentioning
confidence: 96%
“…The catchments included in this volume are located in a wide variety of environments, including high elevation (Holko et al, 2018;Zuecco et al, 2018), pre-alpine (van Meerveld et al, 2018, and sub-Mediterranean (Lana-Renault et al, 2018;Llorens et al 2018) mountain areas; in rural landscapes under both humid (Gascuel-Odoux et al, 2018) and Mediterranean (Schnabel et al, 2018) conditions; and in environments in transition between arid and semiarid climate conditions (Rodríguez-Caballero et al, 2018). Most of the contributions focus on understanding of runoff generation mechanisms in the studied environments, using various types of data (hydrometric data, isotopes, stream chemistry) and approaches (analysis of thresholds, hysteresis, hydrological connectivity, controlling factors, and hydrological modeling).…”
Section: This Volume Of Cuadernos De Investigación Geográfica-geograpmentioning
confidence: 99%